Multiparametric autoimmune diagnostics: recent advances - Damoiseaux J (Dove Medical Press, 2016)
Jan Damoiseaux Central Diagnostic Laboratory, Maastricht University Medical Centre, Maastricht, the Netherlands Abstract: Autoimmune diagnostics in a routine clinical laboratory is constantly challenged by the discovery of new autoantibodies and technical innovations in the immunoassays applied. These challenges are, in particular, combined in the multiparametric immunoassays. Appropriate positioning of multiparametric immunoassays within the laboratory requires integrated knowledge of the clinical performance of the test system for each individual antigen, the conditions prescribed in disease criteria and/or guidelines, and the demands of the clinicians. This review provides a summary of the multiparametric immunoassays available, as well as the applications and restrictions in routine clinical practice. Keywords: autoantibodies, line immunoassay, dot immunoassay, addressable laser bead immunoassay, indirect immunofluorescence